Factors affecting the willingness to pay for implants: A study of patients in Riyadh, Saudi Arabia - Bishi Al Garni; Sharat Chandra Pani; Adel AlMaaz; Ehsan Al Qeshtaini; Hamad Abu-Haimed; Khalid Al Sharif (Wolters Kluwer Medknow Publications, 2012)
Background: One of the factors that dissuade patients needing tooth replacement from choosing dental implants is the prohibitive cost. Willingness to pay (WTP) is a useful tool to determine the ideal cost of an expensive procedure. Aim: The aim of this study was to study the factors that influence the willingness to pay (WTP) among patients attending a private clinic and compare them to those attending a government setup. Materials and Methods: A total of 100 patients (38 male, 62 female) who had one or more missing teeth were presented with different cost-benefit scenarios and then asked if they were willing to pay the median cost of a single implant in Riyadh city. The mean WTP price was compared using the one way-ANOVA, factors which could possibly influence patients' WTP were grouped together in a Binomial logistic regression model. Results: Of the 100 individuals surveyed 67% said they would be willing to pay the median price for the placement of an implant. A comparison of socio-demographic factors showed that significant differences were found between gender, income groups and setting of the clinic in the mean WTP price of the patients (P < 0.05). We also found that there was a significant difference in the mean WTP price between groups with regard to the area of the missing tooth, the patients' perception of their oral health and the their desire to want an implant (P < 0.05). Conclusion: The majority of the patients surveyed were willing to pay the median price for an implant. Willingness to pay (WTP) is a multifactorial variable which is significantly influenced by the income of the patient, the setting of the clinic and the gender; the most significant factor being the acceptability of the implant to the patient.